Evaluation of attitudes towards thinking and learning in a CALL web site through CMC participation - Zaphiris, Panayiotis; Laghos, Andrew (My University, 2007)
Computer-Mediated-Communication (CMC) is fast becoming a big part of our daily lives. More and more people are increasingly using the computer to communicate and interact with each other. The internet and its advantages of connectivity, enable CMC to be used from a plethora of applications. Most common uses of CMC include email communication, discussion forums as well as real time chat rooms and audio/video conferencing. By communicating through computers and over the internet, online communities emerge. Discussion boards and other CMC applications offer a huge amount of information and the analysis of this data assists in understanding these online communities and the social networks that form around them. There have been various frameworks by different researchers aimed at analyzing CMC. This chapters main objective is to provide an overview of the models and frameworks available that are being used for analyzing CMC in e-Learning environments. The significance of the proposed presentation is that it aims to provide the reader with up-to-date information regarding these methods. Advantages and disadvantages of each of the CMC analysis methods are presented and suggestions for future research directions are made. Finally, these suggestions are applied to a characteristic scenario in e-Learning.